Ionotropic glutamate receptor expression in human white matter. (6th September 2016) - Christensen, Pia Crone; Samadi-Bahrami, Zahra; Pavlov, Vlady; Stys, Peter K.; Moore, G.R. Wayne
Highlights: iGluRs are expressed in normal human white matter. AMPA receptor subunit GluA4 is expressed on oligodendrocytes, myelin and on axons. NMDA receptor subunit GluN1 is expressed on oligodendrocytes and myelin. Results confirm findings reported in the literature from rodent white matter. Abstract: Glutamate is the key excitatory neurotransmitter of the central nervous system (CNS). Its role in human grey matter transmission is well understood, but this is less clear in white matter (WM). Ionotropic glutamate receptors (iGluR) are found on both neuronal cell bodies and glia as well as on myelinated axons in rodents, and rodent WM tissue is capable of glutamate release. Thus, rodent WM expresses many of the components of the traditional grey matter neuron-to-neuron synapse, but to date this has not been shown for human WM. We demonstrate the presence of iGluRs in human WM by immunofluorescence employing high-resolution spectral confocal imaging. We found that the obligatory N-methyl-d -aspartic acid (NMDA) receptor subunit GluN1 and the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit GluA4 co-localized with myelin, oligodendroglial cell bodies and processes. Additionally, GluA4 colocalized with axons, often in distinct clusters. These findings may explain why human WM is vulnerable to excitotoxic events following acute insults such as stroke and traumatic brain injury and in more chronic inflammatory conditions such as multiple sclerosis (MS). Further exploration of human WM glutamate signalling could pave the way for developing future therapies modulating the glutamate-mediated damage in these and other CNS disorders.